Limited gains in native parasitoid performance on an invasive host beyond three generations of selection - Shelley Linder; Benjamin J. M. Jarrett; Philip Fanning; Rufus Isaacs; Marianna Szűcs (Evolutionary Applications, 2022)
Abstract Co‐evolved natural enemies provide sustainable and long‐term control of numerous invasive insect pests, but the introduction of such enemies has declined sharply due to increasing regulations. In the absence of co‐evolved natural enemies, native species may attack exotic invasive pests; however, they usually lack adaptations to control novel hosts effectively. We investigated the potential of two native pupal parasitoids, Pachycrepoideus vindemmiae and Trichopria drosophilae, to increase their developmental success on the invasive Drosophila suzukii. Replicated populations of the two parasitoids were subjected to 10 generations of laboratory selection on D. suzukii with Drosophila melanogaster serving as the co‐evolved host. We assessed developmental success of selected and control lines in generations 0, 3, and 10. Changes in host preference, sex ratio, development time, and body size were measured to evaluate correlated responses with adaptation. Both parasitoid species responded rapidly to selection by significantly increasing their developmental success on the novel host within three generations, which remained constant for seven additional generations without further improvement. The generalist parasitoid species P. vindemmiae was able to reach similar developmental success as the control populations, while the performance of the more specialized parasitoid T. drosophilae remained lower on the novel than on the co‐evolved host. There was no increase in preference towards the novel host over 10 generations of selection nor were there changes in development time or body size associated with adaptation in either parasitoid species. The sex ratio became less female‐biased for both parasitoids after three generations of selection but rebounded in P. vindemmiae by generation 10. These results suggest that a few generations of selection may be sufficient to improve the performance of native parasitoids on invasive hosts, but with limits to the degree of improvement for managing invasive pests when exotic co‐evolved natural enemies are not available.